INTERCULTURAL PERSPECTIVES ON RESEARCH WRITING, editado por Pilar Mur-Dueñas y Jolanta Šinkūnienė (Amsterdam/Philadelphia: John Benjamins, 2018) - Sánchez-Jiménez, David (Miscelánea: A Journal of English and American Studies, 2021)
-